Awareness and Coping with Emotion in Schizophrenia: Acceptability, Feasibility and Case Illustrations. (4th April 2013) - Caponigro, Janelle M.; Moran, Erin K.; Kring, Ann M.; Moskowitz, Judith T.
<x xml:space="preserve">Abstract</x> Although current treatments help to alleviate some of the symptoms of schizophrenia, people with schizophrenia often continue to experience residual symptoms. An emotion‐focused treatment approach may help to improve well‐being in this population by increasing positive experiences and resources. In this article, we discuss the feasibility and acceptability of a skills‐based group treatment for people schizophrenia or schizoaffective disorder. As part of the Awareness and Coping with Emotion in Schizophrenia (ACES) intervention, group members learned eight empirically supported cognitive and behavioural skills covering emotional awareness and coping. Group member feedback and three case illustrations illuminate participants' experiences with the group, as well as the potential benefits and challenges of this treatment approach. These data suggest that ACES is a feasible and acceptable group intervention. Future research is needed to examine whether ACES has a selective impact on well‐being, but these initial findings point to the promise of this intervention to improve quality of life for individuals with schizophrenia and schizoaffective disorder, thus filling a void in existing treatments options. Copyright © 2013 John Wiley & Sons, Ltd. Key Practitioner Message There is a void in existing treatments for schizophrenia with few interventions focusing on increasing well‐being in this population. Awareness and Coping with Emotion in Schizophrenia (ACES) is a skills‐based group intervention that teaches cognitive and behavioural interventions to promote awareness and coping with emotion. Preliminary evidence demonstrates the feasibility and acceptance of the ACES group intervention in increasing well‐being in those with schizophrenia. Future studies should extend this work by systematically evaluating the efficacy of this treatment approach.